Retroperitoneal undifferentiated pleomorphic sarcoma with total nephrectomy: a case report and literature review - Yu, Kai; Wang, Lan; Bu, Fan; Zhang, Jingxuan; Hai, Yubin; Hu, Rui; Lu, Ji; Shi, Xiaoju (Frontiers in Surgery, 2023)
Background: Undifferentiated sarcoma pleomorphic (UPS) is a highly malignant soft tissue sarcoma with a poor prognosis and no clear effective clinical means for treatment, and there has been no significant progress in research within this field in recent years. The aim of the study was to investigate the epidemiology, etiology, clinical features, diagnostic modalities, various treatment modalities and prognosis of retroperitoneal undifferentiated pleomorphic sarcoma, and to contribute to the clinical treatment of the same type of disease. In this study, we report a case of undifferentiated pleomorphic sarcoma with a primary origin in the retroperitoneum. Undifferentiated pleomorphic sarcoma occurring in the retroperitoneum is rarely reported. Case Description: A 59-year-old man with abdominal distension and pain for 4 months presented to our hospital after conservative treatment had failed. A 9.6cmx7.4cm mass in the left retroperitoneum was revealed by CT scan of the whole abdomen + three stages of enhancement. After surgical treatment, the tumor and the left kidney were completely removed, and pathological examination and genetic sequencing apparently showed undifferentiated pleomorphic sarcoma. The patient subsequently declined follow-up treatment and is currently living in good condition. Conclusions: At the current level of clinical technology, the treatment of undifferentiated pleomorphic sarcoma is still in the exploratory stage, and the scarcity of clinical cases of this disease may have hindered the acquisition of clinical trials and research data for this disease. At present, the first choice of treatment for undifferentiated pleomorphic sarcoma is still radical resection. In the existing clinical studies, there is no strong data to support the effect of preoperative neoadjuvant chemoradiotherapy and adjuvant chemoradiotherapy in clinical practice. Similar to other diseases, the application of radiotherapy and chemotherapy before and after surgery may be a potential treatment for this disease in the future. Targeted therapy for this disease still needs further exploration, and we need more reports on related diseases to promote future treatment and research on this disease.